Hubungan Jumlah Viral Load dengan Kejadian TBC pada Pasien HIV/AIDS yang Mendapatkan Terapi ARV - Andri Baedowi; Zulfian; Hetti Rusmini; Toni Prasetia (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Viral Load (VL) is a direct indicator of the total amount of cells produced by the virus in a person infected with HIV. TB becomes a challenge for controlling Acquired Immunodeficiency Syndrome (AIDS) because it is the most opportunistic infection in people living with HIV / AIDS (PLWHA). TB can increase HIV progression and the risk of death for people living with HIV. Immunosuppression can increase the likelihood that dormant TB germs reactivate. The pathogenesis of TB infection in HIV patients is directly related to the decline in the immune system, specifically CD4 T lymphocytes. HIV infection will cause a decrease in CD4 T lymphocytes thereby reducing the immunological response to Mycobacterium tuberculosis. This will result in reactivation from the latent period of TB to an active infection. This study conducted to discover the relationship between the amount of viral load and the tuberculosis case in HIV / AIDS patients that undertake ARV therapy at RSUD Dr. H. Abdul Moeloek Lampung Province in 2019. Observational analytic approach with cross sectional design was used in this present study. The data taken is secondary data from the medical record of HIV / AIDS patients in Dr. H. Abdul Moeloek Lampung Province in 2019. The sampling technique used was a purposive sampling method and it was obtained a total sample of 196 people. The data was analyzed through Chi Square test. There was a significant relationship between the amount of viral load in HIV / AIDS patients and the tuberculosis case (p-value = 0.004). From the analysis above, it was obtained OR value = 2.52 which represents that patients who have a viral load ≥ 10,000 have a risk of 2.52 times to encounter TB. A high amount of Viral Load can cause immunosuppression in the host and increase the virulence of TB microbes.